A real time trajectory planner for 2-r robotic manipulators - Pires, E. J. Solteiro (2019)
This work proposes a real time algorithm to generate a trajectory for a 2-link planar robotic manipulator. The objective is to minimize the space/time ripple and the energy requirements or the time duration in the robot trajectories. The proposed method uses an off-line genetic algorithm to calculate every possible trajectory between all cells of the workspace grid. The resultant trajectories are saved in several trees. Then any trajectory requested is constructed, in real time, from these trees. The article presents the results for several experiments.